FEATURES OF STORAGE AND TRANSPORTATION OF NARCOTIC ANALGESICS IN CONDITIONS OF EMERGENCY SITUATIONS - P. V. Oliynyk; B. P. Hromovyk (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
The article performs the analysis of the current state regulatory-legal framework relating to the use of narcotic analgesics in health care institutions in emergencies peace and wartime.There are developed recommendations for adapting the requirements for storage and transportation of narcotic analgesics in emergency situations by making amendments to the Law of Ukraine "About narcotic drugs, psy-chotropic substances and precursors" and to the Order of Ministry of Internal Affairs of Ukraine from 15.05.2009 № 216 "About approval of requirements to objects and spaces intended for the implementation of turnover activities in narcotic drugs, psychotropic substances and precursors".